The Sign of the Green Function of an n-th Order Linear Boundary Value Problem - Almenar Belenguer, Pedro; Jódar, Lucas (Mathematics (Basel), 2020)
This paper provides results on the sign of the Green function (and its partial derivatives) of an n-th order boundary value problem subject to a wide set of homogeneous two-point boundary conditions. The dependence of the absolute value of the Green function and some of its partial derivatives with respect to the extremes where the boundary conditions are set is also assessed.